Explaining Trade Flows : Traditional and New Determinants of Trade Patterns - Gourdon, Julien (2012)
An empirical tradition in international trade seeks to establish whether the predictions of factor abundance theory match with the data. In this paper, we test if the "new" determinants used in the factor content version of H-O-V models (differences in productivity, in returns to scale or in consumers' preferences) help us to improve our estimation of trade patterns in commodities. The results show that conventional factors are still important in determining trade structure although new determinants need to be included to determine comparative advantage. Turning to the change across periods, differences in factor endowments have not diminished over time: we observe an increase in specialization according to skill endowment. Hence, those "new" determinants are not new forces that drive trade flows.